Enhanced separation of coal bed methane via bioclathrates formation. (1st May 2019) - Sun, Qiang; Chen, Bo; Li, Yangyang; Yuan, Gaoqiang; Xu, Zhen; Guo, Xuqiang; Li, Xingxun; Lan, Wenjie; Yang, Lanying
Highlights: CH4 /N2 hydrate formation conditions were measured with tea polyphenol and catechin. The formation rate and gas storage capacity of CH4 /N2 bioclathrates were obtained. The enhanced separation of CH4 /N2 via bioclathrate formation was conducted. Biopromoter can promote the development and application of hydrate separation method. Abstract: The separation and utilization of coal bed methane have great research and economic significances. Consequently, we investigated the two-stage separation of CH4 /N2 binary gas mixture, an analogue of coal bed methane, using hydrate separating method in this work. In order to realize green environmental protection and promote the popularization of hydrate separation method, two biological additives, i.e., tea polyphenol and catechin, were applied to recovery CH4 by forming bioclathrates. The influences of tea polyphenol and catechin on hydrates thermodynamic phase equilibria, kinetic hydration rate, gas storage capacity and separation effects were systematically studied. The results show that these two bio-additives could significantly increase the formation rate and gas storage capacity of hydrates in comparison with pure water system. In addition, the recovery of CH4 and separation factor are also enhanced in the presence of bio-promoters. Therefore, the formation of bioclathrates is helpful to protect environment, and promote the industrial application of the hydrate separation technology.